Markers of Sleep Disordered Breathing and Diabetes Mellitus in a Multiethnic Sample of US Adults: Results from the National Health and Nutrition Examination Survey (2005–2008). (13th November 2012) - Sabanayagam, Charumathi; Teppala, Srinivas; Shankar, Anoop
Abstract : We examined gender and ethnic differences in the association between sleep disordered breathing (SDB) and diabetes among 6, 522 participants aged ≥20 years from the National Health and Nutrition Examination Survey 2005–08. SDB severity was defined based on an additive summary score including sleep duration, snoring, snorting, and daytime sleepiness. We found that the summary SDB score was significantly associated with diabetes after adjusting for potential confounders in the whole population. Compared to those without any sleep disturbance, the multivariable odds ratio (OR) (95% confidence interval (CI)) of diabetes among those with ≥3 sleep disturbances was 2.04 (1.46–2.87). In sex-specific analyses, this association was significant only in women (OR (95% CI) = 3.68 (2.01–6.72)) but not in men (1.10 (0.59–2.04)), P -interaction= 0.01 . However, there were no ethnic differences in this association, P -interaction= 0.7 . In a nationally representative sample of US adults, SDB was independently associated with diabetes only in women, but not in men.